Cholesterol and Glucose Lowering Effect by Some Edible Mushrooms - Hassan, A.; R., Mahmoud (Iraqi Journal of Science, 2025)
Ten species of edible mushrooms (higher fungi) were tested for their ability to reduce cholesterol and glucose in mice blood. The powders of dried fruit bodies of these mushrooms were mixed with standard mice diet at 5 and 10% (on dry wt.). This diet was also supplemented with 2% of pure cholesterol and glucose. Though the significant reduction of blood cholesterol and glucose in mice fed on all tested mushrooms (at both concentrations) was recorded, maximum reduction of blood cholesterol in mice fed on 10% of Pleurotas ostreanus (Gray types, Lentous edodes, Pleurotus ostreatus (White type), Ganoderma lucidum and Pleurotus sajor caju was 52.55, 50, 485, 46.6 and 18.1% in males, and 50,42, 48.72, 46.4, 41.4 and 38.1% in females, respectively, after 4 weeks from feeding On the other hand, maximum reduction of blood glucose in mice fed on 10% of Lentmedies, Cogrimas enmatas, Pleurotus sajor-caju, Pleurona streatur White type) and Ganoderma lucidus was 41, 42, 33.5, 33 and 32% in males 12 and 35% in females, respectively, after 4 weeks from feeding. These results suggest that these edible mushrooms benefit for patients suffering from hypertension, diabetes and obesity.